Circulating follicular regulatory T cells could inhibit Ig production in a CTLA-4-dependent manner but are dysregulated in ulcerative colitis. (October 2019) - Wang, Shaoxuan; Fan, Tingting; Yao, Li; Ma, Ran; Yang, Shaofeng; Yuan, Fang
Abstract: Ulcerative colitis (UC) is a chronic relapsing inflammatory disease that occurs in the gastrointestinal tract, characterized by an upregulation in autoantibody production and antimicrobial antibody production. The interaction between follicular helper T cells (Tfh) and follicular regulatory T cells (Tfr) is critical to the induction and regulation of antibody production. In this study, we investigated the characteristics of Tfr cells in UC patients. We gated circulating Tfr cells as CD4 + CXCR5 + CD25 + CD127 − T cells, of which approximately 73% on average were Foxp3 + . The circulating Tfh (CD4 + CXCR5 + CD25 − ) cells from control subjects and UC patients presented a comparable capacity to induce IgM production from naive B cells and to mediate class switching to IgG. Tfr cells significantly reduced Tfh-mediated B cell help in both healthy controls and UC patients in a concentration-dependent manner. However, the suppression capacity of Tfr cells was significantly lower in UC patients than in healthy controls. Subsequently, we found that the frequency of CTLA-4-expressing cells was only slightly lower in UC patients, but the MFI of CTLA-4, however, was markedly lower in UC patients. CTLA-4 blockade nearly abrogated Tfr-mediated suppression of IgM, and significantly reduced Tfr-mediated suppression of IgG. Moreover, CTLA-4 blockade removed the relative advantage of Tfr suppression capacity in healthy controls compared to UC patients. Overall, this study demonstrated that CTLA-4 was required for Tfr-mediated suppression of B cell help, but was expressed at lower levels in UC patients.